The rationale and design of public involvement in health-funding decision making: focus groups with the Canadian public. (5th December 2020) - Lopes, Edilene; Street, Jackie; Stafinski, Tania; Merlin, Tracy; Carter, Drew
Abstract : Background: Worldwide, governments employ health technology assessment (HTA) in healthcare funding decision making. Requests to include public perspectives in this are increasing, with the idea being that the public can identify social values to guide policy development, increasing the transparency and accountability of government decision making. Objective: To understand the perspectives of the Canadian public on the rationale and design of public involvement in HTA. Design: A demographically representative sample of residents of a Canadian province was selected to take part in two sets of two focus groups (sixteen people for the first set and twenty for the second set). Results: Participants were suspicious of the interests driving various stakeholders involved in HTA. They saw the public as uniquely impartial though also lacking knowledge about health technologies. Participants were also suspicious of personal biases and commended mechanisms to reduce their impact. Participants suggested various involvement methods, such as focus groups, citizens' juries and surveys, noting advantages and disadvantages belonging to each and commending a combination. Discussion and conclusions: We identified a lack of public understanding of how decisions are made and distrust concerning whose interests and values are being considered. Public involvement was seen as a way of providing information to the public and ascertaining their views and values. Participants suggested that public involvement should employ a mixed-methods strategy to support informed debate and participation of a large number of people.